Unveiling behavioural biases under the influence of socio-demographic variables: Evidence from equity investors in Southern Assam - Das, Poonam; Das, Amit Kumar (International journal of economic perspectives, 2026)
With the consistent development of the financial market, equity investors’ investment behaviour has undergone significant changes. The inconsistent practice of rationality by financial market participants causes the existence of market anomalies, leading to persistent deviations from rational pricing that are often unaddressed by the theories of “traditional finance”. On the contrary, the theories of “behavioural finance” delineate how financial market participants systematically deviate from the rationality assumptions in the presence of behavioural biases, resulting in sub-optimal investment decisions. This study primarily explores the existence of behavioural biases among equity market participants in the Southern part of Assam. Based on the average value of the responses corresponding to each behavioural bias, the study finds the prominent presence of “anchoring bias”, followed by “representativeness bias” and “disposition effect” among equity investors of the region. The statistical findings of the “independent sample t-test” and “one-way ANOVA”, confirm a notable difference in “overconfidence bias”, “anchoring bias”, and “herding bias” due to differences in “gender”, “education”, “occupation”, “annual income”, and “investment experience” of the investors. With "multiple regression analysis," the study confirms that demographic variables of the investors significantly affect behavioural biases, especially, a notable variation is observed in “overconfidence bias” due to the difference in demographic determinants of equity investors.